Human-like hopping in machines: Feedback- versus feed-forward-controlled motions - Oehlke, Jonathan; Beckerle, Philipp; Seyfarth, Andre; Sharbafi, Maziar A. (Biological Cybernetics, 2019)
Template models of legged locomotion are powerful tools for gait analysis, but can also inspire robot design and control. In this paper, a spring-loaded inverted pendulum (SLIP) model is employed to control vertical hopping of a 2-segmented legged robot. Feed-forward and bio-inspired virtual model control using the SLIP model are compared. In the latter approach, the feedback control emulates a virtual spring between hip and foot. The results demonstrate similarity of human and robot hopping. Moreover, the feedback control proves to simplify and improve hopping control. It yields better perturbation recovery and locomotion adaptation and is even easier to tune. Thus, human-like hopping is achievable using a rather simple template-based controller, which ensures the required performance, robustness and versatility.
CRIS-Team Scopus Importer:2021-09-24
Keywords: Energy management; Hopping with segmented leg; Template-based control; Virtual model control